2013
DOI: 10.1364/oe.21.015514
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of acoustic sensitivity of hollow-core photonic bandgap fibers

Abstract: The acoustic pressure sensitivities of hollow-core photonic bandgap fibers (HC-PBFs) with different thicknesses of silica outercladding and polymer jacket were experimentally investigated. Experiment with a HC-PBF with 7 μm-thick silica outer cladding and 100 μm-thick Parylene C jacket demonstrated a pressure sensitivity 10 dB higher than the commercial HC-1550-02 fiber and 25 dB higher than a standard single mode fiber. The significant enhancement in sensitivity would simplify the design of fiber hydrophone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 22 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…The microstructured regions of the PCFs are modeled as anisotropic materials while the silica outer cladding and the acrylate regions are modeled as isotropic materials [11]. The effect of the coating material and thickness on NR was proposed by many researchers and recently in [12]. To avoid inaccurate comparison between the three investigated fibers because of different coating materials and thickness, the same coating material and thickness for all fibers are used.…”
Section: Simulation Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The microstructured regions of the PCFs are modeled as anisotropic materials while the silica outer cladding and the acrylate regions are modeled as isotropic materials [11]. The effect of the coating material and thickness on NR was proposed by many researchers and recently in [12]. To avoid inaccurate comparison between the three investigated fibers because of different coating materials and thickness, the same coating material and thickness for all fibers are used.…”
Section: Simulation Results and Analysismentioning
confidence: 99%
“…Some of these advantages are; (1) design and manufacturing flexibility of HC-PBFs can reduce the effective Young's modulus of the fiber and enhances the NR of the HC-PBF [3,11], (2) the undesirable negative index effect introduced in SMF is expected to be greatly reduced in a HC-PBF in which most of the mode energy is confined in air, so the NR of the HC-PBF is expected to have higher sensitivity, (3) holes of the HC-PBF can be filled with a material with opposite thermal expansion to make the material completely temperature insensitive [9], (4) In the HC-PBF sensing coil, because the light travels through air, it has much smaller Kerr, Faraday, and thermal constants than silica cores, this reduces the dependencies on power, magnetic field, and temperature fluctuations [9], (5) HC-PBFs are almost entirely bend-insensitive and can be bent down to very small diameters (<1cm) with minimal loss, this makes it suitable for small-size hydrophone applications [5,12], and (6) HC-PBFs have very low back-reflection at the fiber end faces because of the close match of the mode index with the ambient air and this helps to reduce the back-reflected light level which is beneficial for many applications [10]. However, using PCFs as acoustic sensors needs further investigation to be feasible as an alternative to its counterpart of SMF interferometers.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic pressures with different amplitudes and frequencies that act on the investigated optical fiber are applied by the ASI. Once the induced stress distribution in the optical fiber is calculated, the anisotropic refractive index elements are calculated using (8), and the EMW module is used for mode analysis. Mode analysis study allows us to calculate eff , eff , MFD, and NA.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Some of these advantages are as follows. (1) The design and manufacturing flexibility of HC-PBFs reduces the effective Young's modulus of the fiber and enhances the NR of the HC-PBF to acoustic pressure [2], (2) matching between the mode indexes of the HC-PBF with the ambient air helps to reduce the back-reflected light at the fiber end faces which is useful for many applications [7], (3) holes of the HC-PBF can be filled with a substance with opposite thermal expansion to make the material insensitive to temperature [5], (4) in the HC-PBF, because the optical mode propagates in air, it has smaller Faraday, Kerr, and thermal constants than solid-silica cores, and this reduces the dependencies on temperature, magnetic field, and power fluctuations [5], and (5) HC-PBFs are almost entirely bend-insensitive and can be bent to very small diameters (<1 cm) with minimal loss, and this makes it suitable for small-size hydrophone systems [6,8]. However, using HC-PBFs as underwater acoustic sensors needs further investigation to be feasible alternatives to their 2 International Journal of Optics counterparts of SMFs.…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al reported the enhancement of the acoustic sensitivity with hollow-core photonic bandgap fibers (HC-PBFs) by using air-included polymer coatings [43]. The first investigations in this field were performed by Cole et al, where it was demonstrated that this type of coated fiber has similar normalized responsivity (NR) to the mandrel based hydrophones [44,45].…”
Section: Enhancement Of Acoustic Sensitivity Of Hollow-core Photonic mentioning
confidence: 99%